STRATEGI KOMUNIKASI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN BANYUMAS DALAM MENINGKATKAN LITERASI DIGITAL BAGI MAHASISWA - Sabila Yusrina; Anas Azhimi Qalban (Lembaga Sepercenter, 2026)
Digital literacy has become one of the most important competencies in the information technology era, especially for students as agents of change. The Communication and Information Agency (Diskominfo) of Banyumas Regency has a strategic role in improving digital literacy through various communication programmes. This study aims to analyse the communication strategies implemented by Diskominfo Banyumas in improving digital literacy among students. The research method used a qualitative approach with data collection techniques through in-depth interviews, observation, and document analysis. The results of the study indicate that Diskominfo Banyumas implements communication strategies through three main approaches: (1) Education through Social Media and Websites, (2) Training and Workshops, and (3) Collaboration with Higher Education Institutions. Challenges faced include budget constraints, student participation, and dynamic technological adaptation. Recommendations from this study include strengthening collaboration with universities, improving creative content, and conducting continuous evaluation to ensure the effectiveness of the programme.